I Can See Clearly Now: Episodic Future Thinking and Imaginability in Perceptions of Climate-Related Risk Events - Bø, Simen; Wolff, Katharina (Frontiers in Psychology, 2020)
Climate change is statistical, abstract and difficult to comprehend directly. Imagining a specific, personal episode where you experience consequences of climate change in the future (episodic future thinking) may bring climate change closer, thus increasing the perceived risk of climate-related risk events. We conducted an experiment to test whether episodic future thinking increased the perceived risk of climate-related risk events and climate change in general, as compared to thinking about the future in a general, abstract manner (semantic future thinking). We also tested whether this effect is moderated by how easy it is to imagine the specific climate-related risk event initially. Participants were randomly assigned to an episodic future thinking-condition or a semantic future thinking-condition, and two of the risk events in each condition were related to flooding (difficult to imagine) and two were related to extreme temperature (easy to imagine). The results show no main effect of episodic future thinking on perceived risk, and no interaction effect with imaginability. Contrary to expectations and earlier research, this suggests that episodic future thinking may not influence risk perception.